2009
DOI: 10.1158/1078-0432.ccr-08-2628
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Mammary Carcinomas in HER-2 Transgenic Mice through Combination of Genetic Vaccine and an Agonist of Toll-Like Receptor 9

Abstract: Purpose: Oligodeoxynucleotides containing unmethylated CpG dinucleotides induce innate and adaptive immunity throughToll-like receptor 9 (TLR9). In the present study, we have examined the ability of a novel agonist of TLR9, called immunomodulatory oligonucleotide (IMO), to enhance effects of a HER-2/neu plasmid DNA electroporation/adenovirus (DNA-EP/Ad) vaccine. Experimental Design: BALB/NeuT mice were treated with DNA-EP vaccine alone, IMO alone, or the combination of two agents starting at week 13, when all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…This may be important because Garbi et al have shown that proper activation of endothelium is crucial for the extravasation of tumor-specific T cells from the blood into cancerous tissues (49). The results are also in agreement with the recent two studies documenting that DNA or peptide vaccine in combination with TLR-9 agonists could effectively prevent and treat spontaneous mammary carcinomas in neu-transgenic mice (48,50).…”
Section: Discussionsupporting
confidence: 84%
“…This may be important because Garbi et al have shown that proper activation of endothelium is crucial for the extravasation of tumor-specific T cells from the blood into cancerous tissues (49). The results are also in agreement with the recent two studies documenting that DNA or peptide vaccine in combination with TLR-9 agonists could effectively prevent and treat spontaneous mammary carcinomas in neu-transgenic mice (48,50).…”
Section: Discussionsupporting
confidence: 84%
“…23,40,41 Given the importance of antibodies in anti-HER-2/neu immunity, potent immunotherapy regimens against HER-2/neu-positive tumors may be designed by combining hN'-neu-shFoxo3 DNA vaccination with passive immunization with anti-p185neu antibodies. Furthermore, other strategies that can elicit both strong antibody and T-cell immune responses to the HER-2/neu antigen, such as the addition of mLAG-3Ig 42 or a TLR-9 43 agonist in the DNA vaccination or the fusion of the extracellular domain of the CTLA-4 to the HER-2/neu, 44 may confer synergistic antitumor effects against HER-2/neu-positive tumors and could be attractive regimens for translation to a clinical setting. In summary, for the first time, we present evidence demonstrating that the silencing of Foxo3 in DCs in vivo by the HER-2/neu DNA vaccine represents an innovative and effective approach to enhance the HER-2/neu antigen-specific CD8 + T-cell immune responses and therapeutic antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…This might be caused partly by the immunosuppressive environment of tumors (13). However, preclinical data suggests that by increasing costimulatory "danger" signals, immunosuppressive mechanisms could be overridden (4,13,14). Oncolytic replication provides strong danger signals and lysis of tumor cells releases tumor-associated antigens for sampling (15).…”
Section: Introductionmentioning
confidence: 99%